Creativity and reason in cognitive development - Kaufman, James C.; Baer, John. (Cambridge : Cambridge University Press, 2006)
What factors might influence a decline in creativity and imagination? Is there something about the development of one kind of thinking that undermines imaginative and creative thinking? This book explores these questions from a variety of perspectives. Essays from psychologists and educators discuss the relationships among creativity, reason, and knowledge.
Includes bibliographical references and indexes.
Keywords: Creative thinking in children; Creative ability in children; Learning, Psychology .; Cognition in children